Detection of human papillomavirus in oral warts using in situ hybridization - Suzana Orsini Machado de Sousa; Oliver Guilherme da Silva; Péricles Martim Reche; Renata Rodrigues Acay; Cristhiane Almeida Leite (Faculdade São Leopoldo Mandic, 2008)
Objective: The human papillomavirus is a group of DNA epitheliotrophic viruses associated with the etiology of benign and malignant oral warts. More than 100 types have been identified and among them, 24 have been found into the oral cavity. The aim of this study was to analyze human papillomavirus prevalence and its subtypes in 50 oral warts, of which 20 were squamous papillomas, 17 condylomaacuminatum and 13 verruca vulgaris. Method: In situ hybridization was used with biotinylated DNA probes for wide-spectrum HPV and with specific probes for human papillomavirus 6/11, human papillomavirus 16/18 and human papillomavirus 31/33. Results: Human papillomavirus was present in ten (20%) of the 50 oral wart cases, 03 (3/20) squamous papillomas, 05 (5/17) condyloma acuminatum and 02 (2/13) verruca vulgaris. Of these, 8 (16%) were positive to the HPV probe 6/11 being 5 condyloma acuminatum, 1 squamous papilloma and 2 verruca vulgaris. Three cases (6%) demonstrated positivity to the human papillomavirus probe 16/18, with 2 being cases of condyloma and the other a case of squamous papilloma. Of the six positive cases to the human papillomavirus probe 31/33, (12%) 4 were condyloma acuminatum and 2 squamous papillomas. Conclusion: The human papillomavirus expression (20%) found in this study was low, but within the average found in the literature. Nonetheless, in addition to in situ hybridization, other methods may be necessary for confirming the presence of human papillomavirus.